Pengembangan Video Iklan Menggunakan Metode Live Shoot Sebagai Sarana Promosi - Muyassar Raihan Mahdy (The Indonesian Journal of Computer Science Research, 2023)
Promotion is an action or activity carried out to attract interest in buying a product or service. Promotion mix has a positive relationship with purchasing decisions because consumers will be introduced to various products which will influence consumers' desire to buy products. Mix Marketing is a series of strategies to increase the number of customers and company income. The promotion strategy is also a way to manage communication between sellers and buyers in getting feedback on their services. Krisbar is a susi chicken food stall that is currently growing. This business has a target market of students throughout the city of Yogyakarta but has not achieved maximum results because it is not well known among Yogyakarta students. One of the efforts in promoting this business requires advertisements that will be displayed on all social media, both Instagram, Facebook, and other social media. Based on this description, the purpose of this research is to build video advertisements using the live shoot method as a promotional medium for Krisbar. Data collection was carried out for 10 days from 1-10 November 2022 with video capture in several places in the Krisbar environment. The data collection tools are digital cameras and smartphones and then data processing is carried out in the form of video editing using Adobe Premiere software.